Optimization of PV-BESS System Capacity Considering Battery Degradation for Nighttime Peak Load Supply: A Case Study of Guluk-Guluk, Madura - Herdian Raditya; Rachmawan Budiarto; Roni Irnawan (Green Publisher Indonesia, 2026)
The integration of photovoltaic (PV) generation into power systems presents operational challenges due to the temporal mismatch between daytime solar production and nighttime peak demand. This issue is particularly critical in tropical systems with limited local generation flexibility, such as Guluk-Guluk, Madura, where a PV–battery energy storage system (PV-BESS) is planned to support nighttime peak load demand. This study aimed to determine the optimal PV-BESS capacity configuration under a PV-only charging scheme, in which the battery is charged solely by PV generation without grid support. A 25-year time-series simulation based on historical solar resource data was integrated with Particle Swarm Optimization (PSO) to minimize the Net Present Cost (NPC) while penalizing unmet energy demand. Battery degradation was modeled using calendar and cycle aging, and the impact of Power Conversion System (PCS) charging capacity was evaluated through sensitivity analysis and re-optimization. The baseline optimal configuration consisted of 75.36 MWp of PV capacity and 570.98 MWh of initial BESS capacity with a 50 MW PCS, achieving 83.85% reliability and an NPC of USD 269.18 million. The results indicated that battery aging was not the dominant factor limiting system reliability; instead, daily solar variability and PCS charging constraints had stronger impacts. Increasing PCS capacity from 50 MW to approximately 56 MW significantly improved reliability, while further increases yielded diminishing returns as the system transitioned from power-limited to energy-limited operation. These findings emphasize the importance of integrated PV, BESS, and PCS planning for renewable peaker applications in tropical power systems.